Implementation of the Right to Remission for Prisoners of Narcotics Abuse in Lapas 1 Medan - Merry Roseline Pasaribu; Winona Silvy Noviyanti S; Rachel Lasria Naibaho (Journal of Law, Politic and Humanities, 2024)
This research aims to find out the fulfillment of remission rights for narcotics abuse inmates in Lapas 1 Medan. Prisoners who have rights that are protected from human rights and which are regulated in Law Number 12 of 1995 concerning Corrections in Article 14 paragraph (1) explains the rights of prisoners, one of which is the right to get remission. Remission is the right of every prisoner that must be fulfilled. However, Government Regulation Number 99 of 2012 concerning the Second Amendment to Government Regulation Number 32 of 1999 concerning Conditions and Procedures for the Implementation of Rights and Prisoners of Corrections tightens the granting of remission to prisoners of narcotics crimes.